Carotid surgical cut-down technique for neuroendovascular therapy. Issue 3 (June 2019) - Takano, Issei; Matsumoto, Yoshiyuki; Fujii, Yoshiko; Inoue, Yuki; Sugiura, Yoshiki; Kawamura, Yosuke; Suzuki, Ryotaro; Nakae, Ryuta; Tanaka, Yoshihiro; Nagaishi, Masaya; Takigawa, Tomoji; Hyodo, Akio; et al.
Background: Neuroendovascular therapy is typically performed via the femoral artery, but there are rare cases in which a tortuous upstream angioarchitecture makes it difficult to access the intracranial circulation via this route. Methods: In this case series, we describe six cases treated by surgical cut-down in the neck, with puncture of the carotid artery. Antiplatelet and anticoagulation agents were used in all cases. The indications for the technique were postsurgical thoracic aortic aneurysm (two cases), postsurgical abdominal aortic aneurysm (one case), major vessel tortuosity of the common carotid artery (two cases) and aortic arch anomaly (one case). Results: The surgical cut-down technique permitted successful neuroendovascular therapy. Although one patient had a small cervical haematoma, he was treated without surgical evacuation. Conclusion: Overall, our findings indicate that the surgical cut-down technique is safe and useful for patients in whom the femoral approach is unsuitable.